PERLINDUNGAN HUKUM PEREMPUAN DAN ANAK KORBAN HUMAN TRAFFICKING DALAM PERSPEKTIF VIKTIMOLOGI (STUDI DI KABUPATEN BANYUMAS) - Hendriana, Rani; Widyaningsih, Rindha; Sari, Dessi Perdani Yuris Puspita (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Legal protection to women and children as human trafficking victims in Banyumas, to date, has not been viewed in victimology perspective. Intriguing issues have been analyzed regarding legal protection and factors that tend to inhibit its implementation in victimology perspective. This study used a qualitative research method and sociological juridical approach. The results showed that the third goal of victimology has not been reached, in which the legal protection is not yet fully leads to the needs of victims. The main factor that tends to influence is the correlation between the victim’s fault in the occurrence of human trafficking and the victim's response to legal protection, while other inhibiting factors are the legal structure, legal substance, and society legal culture.Keywords: legal protection, women, children, human trafficking, victimology